International Food Policy Research Institute (IFPRI) policy on dataset management 2010 - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
IFPRI's mandate is to conduct policy research and outreach that have positive impacts on the lives of poor and malnourished people. Increasing access to the data assembled by IFPRI staff and collaborators, while safeguarding the privacy of participants and protecting confidential and proprietary information, will enhance IFPRI's ability to carry out this mandate. The purpose of this policy is to assist IFPRI research divisions and researchers in managing the storage of, retention of, and access to data and records associated with research activities.